Cycloartane Triterpenoids Acid from Garcinia eugenifolia - Jong, V.Y.M.; Ee, G.C.L.; Sukari, M.A.; Taufiq-Yap, Y.H.; Khong, H.Y. (Asian Journal of Chemistry, 2012)
A study on the roots of Garcinia eugenifolia has resulted in the isolation of one cycloartane triterpenoid acid i.e., magniferolic acid (1). This is a first isolation and report on this compound from Garcinia eugenifolia. Three other triterpenes which are euphadienol (2), b-sitosterol (3) and friedelin (4) were also obtained. Besides this, the ketone (3-hydroxyphenyl)3,4,5-trihydroxyphenyl)methanone (5) and two xanthones, 5,9-dihydroxy-8-methoxy-2,2-dimethyl-7-(3-methylbut-2-enyl)pyrano[3,2-b]xanthen-6(2H)-one (6) and 1,3,6,8-tetrahydroxyxanthone (7) were also obtained from this plant.